Approximate nonparametric corrected-score method for joint modeling of survival and longitudinal data measured with error - de Dieu Tapsoba, Jean; Lee, Shen-Ming; Wang, C. Y. (Biometrical journal, 2011)
We consider the problem of jointly modeling survival time and longitudinal data subject to measurement error. The survival times are modeled through the proportional hazards model and a random effects model is assumed for the longitudinal covariate process. Under this framework, we propose an approximate nonparametric corrected‐score estimator for the parameter, which describes the association between the time‐to‐event and the longitudinal covariate. The term nonparametric refers to the fact that assumptions regarding the distribution of the random effects and that of the measurement error are unnecessary. The finite sample size performance of the approximate nonparametric corrected‐score estimator is examined through simulation studies and its asymptotic properties are also developed. Furthermore, the proposed estimator and some existing estimators are applied to real data from an AIDS clinical trial.